Relative Importance of Chemoautotrophy for Primary Production in a Light Exposed Marine Shallow Hydrothermal System - Gomez-Saez, Gonzalo V.; Pop Ristova, Petra; Sievert, Stefan M.; Elvert, Marcus; Hinrichs, Kai-Uwe; Bühring, Solveig I. (Frontiers in Microbiology, 2017)
The unique geochemistry of marine shallow-water hydrothermal systems promotes the establishment of diverse microbial communities with a range of metabolic pathways. In contrast to deep-sea vents, shallow-water vents not only support chemosynthesis, but also phototrophic primary production due to the availability of light. However, comprehensive studies targeting the predominant biogeochemical processes are rare, and consequently a holistic understanding of the functioning of these ecosystems is currently lacking. To this end, we combined stable isotope probing (SIP) of lipid biomarkers with an analysis of the bacterial communities to investigate if chemoautotrophy, in parallel to photoautotrophy, plays an important role in autotrophic carbon fixation and to identify the key players. The study was carried out at a marine shallow-water hydrothermal system located at 5 m water depth off Dominica Island (Lesser Antilles), characterized by up to 55 °C warm hydrothermal fluids that contain high amounts of dissolved Fe2+. Analysis of the bacterial diversity revealed Anaerolineae of the Chloroflexi as the most abundant bacterial class. Furthermore, the presence of key players involved in iron cycling generally known from deep-sea hydrothermal vents (e.g. Zetaproteobacteria and Geothermobacter), supported the importance of iron-driven redox processes in this hydrothermal system. Uptake of 13C-bicarbonate into bacterial fatty acids under light and dark conditions revealed active photo- and chemoautotrophic communities, with chemoautotrophy accounting for up to 65% of the observed autotrophic carbon fixation. Relatively increased 13C-incorporation in the dark allowed the classification of aiC15:0, C15:0 and iC16:0 as potential lipid biomarkers for bacterial chemoautotrophy in this ecosystem. Highest total 13C-incorporation into fatty acids took place at the sediment surface, but chemosynthesis was found to be active down to 8 cm sediment depth. In conclusion, this study highlights the relative importance of chemoautotrophy compared to photoautotrophy in a shallow-water hydrothermal system, emphasizing chemosynthesis as a prominent process for biomass production in marine coastal environments influenced by hydrothermalism.